Microstructures and properties of friction stir spot welded DP590 dual phase steel sheets. (July 2014) - Sarkar, R.; Pal, T. K.; Shome, M.
<x content-type="archive" xml:space="preserve">Abstract</x> DP590 steel sheets were joined by friction stir spot welding using polycrystalline cubic boron nitride tool with an objective to produce bond diameters similar to conventional spot welding nuggets. A range of spindle rotation (400–2400 rev min−1) and plunge speeds (0·03–3·8 mm s−1) were exercised to attain defect free welds in 1·6 mm thick sheets. A bond diameter of 4t1/2, alike minimum nugget diameter criteria for resistance spot welds, resulted in superior mechanical properties than conventional spot welds. The heat inputs corresponding to different welding parameters influenced the weld microstructure, including grain size, phases and their morphology. The bond diameter was higher for higher heat inputs. However, low heat input welds with weld time cycles ∼4 s produced more refined microstructure and exhibited similar strengths even with reduced bond size. Plug type failure was associated with larger bond diameters (∼7·1 mm), while interfacial failure was observed with smaller welds (∼5·4 mm).